1993
DOI: 10.1021/bi00094a017
|View full text |Cite
|
Sign up to set email alerts
|

Purification and cDNA sequence of an inducible nitric oxide synthase from a human tumor cell line

Abstract: A combination of cytokines induced the expression of nitric oxide synthase (NOS) in a human colorectal adenocarcinoma cell line, DLD-1. We have purified the enzyme and examined some of its biochemical properties. An antiserum to an inducible NOS from murine macrophages cross-reacted with the DLD-1 NOS. The purified human and murine enzymes displayed a similar lack of dependence on exogenous calcium and calmodulin for activity, which contrasts with the requirement for calcium and calmodulin of purified brain an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
89
1
2

Year Published

1995
1995
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(101 citation statements)
references
References 29 publications
9
89
1
2
Order By: Relevance
“…Several tumour cell lines express NO synthases (Forstmann et al, 1990;Sherman et al, 1993;Werner-Felmayer et al, 1993;Jenkins et al, 1994), and we have recently reported NO synthase activity in human ovarian and uterine tumour tissue (Thomsen et al, 1994). The correlation observed between enzyme activity and tumour grade suggests that NO plays a role in the biology of these cancers.…”
mentioning
confidence: 50%
“…Several tumour cell lines express NO synthases (Forstmann et al, 1990;Sherman et al, 1993;Werner-Felmayer et al, 1993;Jenkins et al, 1994), and we have recently reported NO synthase activity in human ovarian and uterine tumour tissue (Thomsen et al, 1994). The correlation observed between enzyme activity and tumour grade suggests that NO plays a role in the biology of these cancers.…”
mentioning
confidence: 50%
“…Prior to assay, the cells were seeded in 96-well plates (2610 5 cells per well) and allowed to attach overnight. NO production induced by exposure of the cells to 200 u ml 71 human interferon-g (hIFN-g), 10 ng human tumour necrosis factor-a (hTNF-a) and 2 ng human interleukin-1b (hIL-1b) for 24 h at 378C (Sherman et al, 1993) was measured with the recently described¯uorescent indicator DAF-FM (Kojima et al, 1999;Nakatsubo et al, 1998). A dimethyl sulphoxide (DMSO; ®nal concentration, 0.02%) solution of DAF-FM (1 mM) and the test compound at a concentration of 0.3 mM ± 1 mM were added at the same time as cytokines.…”
Section: Measurement Of No Production By Dld-1mentioning
confidence: 99%
“…iNOS is found in elevated levels in mammalian tumours [8][9][10] and employing an antisense gene therapy approach could lead to a constriction in tumour vessels and subsequent decrease in oxygenation levels. This artificially hypoxic tumour environment could then be targeted with any novel bioreductive drugs (eg AQ4N 27 ) subsequently shown to be effective in the clinic.…”
Section: Gene Therapymentioning
confidence: 99%
“…Gene Therapy (2000) 7, 1126-1131. pendent manner. Elevated levels of iNOS have been detected in a number of human and mammalian tumour tissues, [8][9][10] although more than one cell type may be expressing the gene. Increased expression of NOS may facilitate the delivery of oxygen and nutrients through the dilated microvessels to the rapidly proliferating tumour cells.…”
Section: Introductionmentioning
confidence: 99%